Workload, Work Stress, and Employee Performance: a literature Review - Riana Nurvianida Nasrul; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2023)
The aim of this paper is to provide a structured literature review on the constructs of workload, work stress, employee performance, and empirical evidence on the relationship between workload, work stress, and employee performance in Indonesia context. 23 (twenty three) papers published during 2018-2022 that investigates workload, work stress, employee performance, and the relationship between workload, work stress, employee performance were reviewed. The results of the review show that workload and work stress have significant effect on employee performance, but the direction of effect varies. 84.61% of 13 (thirteen) empirical results show that workload has a positive effect on employee performance, while the remaining 15.39% has a negative effect. Likewise with work stress. 50.00% of the 10 (ten) empirical results show that work stress has a positive effect, while the remaining 50% has a negative effect. The variety of empirical results requires organizations to determine employee workload and analyze employee work stress carefully, with the hope that these two variables can have a positive impact on employee performance.